2023
DOI: 10.1177/10105395231199559
|View full text |Cite
|
Sign up to set email alerts
|

Does National Health Protection Cover the Vulnerable Groups in Indonesia? A Case Study of Waste Pickers in Surabaya

Yohanes Kambaru Windi,
Charles Livingstone,
Andrea Whittaker

Abstract: The National Health Protection (NHP) of Indonesia is a pro-poor social health insurance as the government pays the monthly premium for the poor. A waste picker is classified as an urban poor group needing affordable or free access to health care. This study explores the extent to which the NHP protects the health of waste pickers and provides them with quality health care. For this mixed-method study, 342 waste pickers completed the survey, 40 engaged in interviews, and 15 participated in Natural Group Discuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…Thus, while health insurance is still required to access outpatient care services, it is insufficient to ensure that food insecure older adults get access to outpatient care. Prior research has revealed that urban poor Indonesians with national health insurance have faced issues such as waiting times, service gaps between fullpaying and subsidized patients, and the inflexibility of the capitation system, par ticularly at PHC providers, 23 which may necessitate addi tional selffunding. As a result of the aforementioned factors, food insecure older adults with low resources may be dis couraged from seeking outpatient care.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, while health insurance is still required to access outpatient care services, it is insufficient to ensure that food insecure older adults get access to outpatient care. Prior research has revealed that urban poor Indonesians with national health insurance have faced issues such as waiting times, service gaps between fullpaying and subsidized patients, and the inflexibility of the capitation system, par ticularly at PHC providers, 23 which may necessitate addi tional selffunding. As a result of the aforementioned factors, food insecure older adults with low resources may be dis couraged from seeking outpatient care.…”
Section: Discussionmentioning
confidence: 99%